Brightburn [videorecording (DVD)] - Yarovesky, David, 1980-; Banks, Elizabeth, 1974-; Denman, David, 1973-; Dunn, Jackson A. (Sony Pictures Home Entertainment, 2019)
A sinister child from another world lands on Earth, and poses a serious threat to mankind.